Making a Reconstruction of the Egtved Clothing - Demant, Ida (Archaeological Textiles Review, 2017)
A reconstruction of the Egtved woman’s clothing dating to the Early Bronze Age (1370 BC) was made for exhibition near the grave in which the originals were found. The clothing consisted of a blouse, belt and corded skirt. Previous observations of the garments were investigated for clues as to the raw materials used and construction methods. Close-up photographs of the originals made further detailed study possible. New observations were made of the wool fibres. Although the project was not primarily intended as experimental archaeology, it offered opportunities for some exploration of the tools and techniques potentially employed in the Early Bronze Age. The project showed it was possible to process the wool fibres using a comb and spinning hook, to weave the blouse on a warp-weighted loom, and that the choice of fleece was crucial to the look and feel of the finished garments. A further outcome of the project was an investigation into how the items were worn and whether they had been previously interpreted accurately for a woman the size of the Egtved woman. The results demonstrated that the clothing did not require the wearer to bare her midriff as had been suggested in the past.